2019
DOI: 10.3390/en12071367
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Coal Gasification Process Simulation with Alkaline Organic Wastewater in a Fluidized Bed Reactor Using Aspen Plus

Abstract: A co-gasification process was proposed both for treating alkaline organic wastewater and to promote coal gasification by the alkaline substances in situ. A catalytic gasification model was developed by introducing a catalytic correction factor to describe the catalytic effects quantitatively. An integrated process simulation was carried out using Aspen Plus equipped with FORTRAN subroutines. The model was verified using the root mean square error between the simulation results and experimental data from the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…The average syngas content was 62.79 vol.% in sawdust gasification, 52.26 vol.% in coal gasification and 64.12 vol.% in SRF gasification. Generally, efficiencies and syngas production rate from coal gasification with entrained flow gasifier shows higher value compared to other feedstocks [26,27]. However, in this study coal gasification showed lower syngas yield and efficiencies than typical coal gasification.…”
Section: Characteristics Of Feedstockscontrasting
confidence: 54%
See 2 more Smart Citations
“…The average syngas content was 62.79 vol.% in sawdust gasification, 52.26 vol.% in coal gasification and 64.12 vol.% in SRF gasification. Generally, efficiencies and syngas production rate from coal gasification with entrained flow gasifier shows higher value compared to other feedstocks [26,27]. However, in this study coal gasification showed lower syngas yield and efficiencies than typical coal gasification.…”
Section: Characteristics Of Feedstockscontrasting
confidence: 54%
“…The optimum ER condition showed the optimum result under the ER value 0.4, which is similar for both sawdust and SRF gasification. In the case of coal gasification, it shows similar efficiencies between ER 0.4 and 0.6 from reference data [26].…”
Section: Gasification Efficiencysupporting
confidence: 52%
See 1 more Smart Citation
“…(1) The entail gasification process is steady state and all considered reactions can achieve chemical equilibrium [36][37][38]. Although there are some slightly differences between these assumptions and the practical process conditions, they are considered reasonable and acceptable by the by comparison in Section 3.1.…”
Section: Assumptions and Stream Parametersmentioning
confidence: 99%
“…The ASPEN simulation of the catalytic co-gasification of coal and organic wastewater with an alkaline pH was investigated by Xiao et al (2019) using a fluidised bed gasifier. The findings revealed that the optimal ratio of steam to coal, temperature, and equivalence ratio for the process.…”
Section: Introductionmentioning
confidence: 99%